FGF receptor genes and breast cancer susceptibility: results from the Breast Cancer Association Consortium - Agarwal, Deepak K.; Brauch, Hiltrud; Brüning, Thomas; Hamann, Ute; Marmé, Frederik; Burwinkel, Barbara; Brenner, Hermann; Dieffenbach, Aida Karina; Arndt, Volker; Chang-Claude, Jenny; Rudolph, Anja; Seibold, Petra Beate (British journal of cancer, 2014)
Breast cancer is one of the most common malignancies in women. Genome-wide association studies have identified FGFR2 as a breast cancer susceptibility gene. Common variation in other fibroblast growth factor (FGF) receptors might also modify risk. We tested this hypothesis by studying genotyped single-nucleotide polymorphisms (SNPs) and imputed SNPs in FGFR1, FGFR3, FGFR4 and FGFRL1 in the Breast Cancer Association Consortium.